Dry eye disease in episodic and chronic migraine: A cross-sectional clinic-based study - Bithi Chowdhury; Pradeep Kumar; Hemant Sharma; Debashish Chowdhury (Cephalalgia Reports, 2024)
Background Dry eye disease (DED) and migraine, two common disorders with public health concerns, may have a bidirectional relationship. Population-based studies have found that migraine patients have higher odds of DED and vice versa. We aimed to evaluate and compare the presence of DED symptoms and objective signs between migraine patients and non-migraine controls. Methods This was a case-control study. We prospectively enrolled 60 consecutive migraine patients (30 episodic and 30 chronic) presenting in the medicine outpatient department, aged 18–65 years, and 60 non-migraine healthy controls visiting the ophthalmology department for refractive errors between February 2019 and June 2021. Consecutive migraine patients and non-migraine healthy controls were assessed in the ophthalmology department at Hindu Rao Hospital, Delhi by the Ocular Disease Surface Index (OSDI) questionnaire for DED symptoms and objectively by measuring tear break-up time (TBUT), Schirmer test (ST), and Fluorescein staining (FS). DED severity was assessed by the Odessey algorithm. Results The mean OSDI score was significantly greater in migraineurs than in controls (31.2 ± 19.8 vs 22.7 ± 15.6; p = 0.010). 45% of migraineurs had DED compared to 18.3% in controls (p = 0.002), whereas 23.3% had severe DED compared to one (1.7%) in the control group (p < 0.001). Migraineurs, compared to controls, had significantly lower mean TBUT (10.1 ± 6.5 s versus 13.4 ± 5.8 s; p = 0.004), higher FS grade (1.57 ± 1.4 versus 0.92 ± 1.2; p = 0.008) and lower ST scores (11.5 ± 5.8 mm versus 14.2 ± 6.2 mm; p = 0.014). Migraineurs with DED, compared with those without DED, had longer migraine disease duration, higher frequency, pain severity, and disability. Compared to episodic migraine, chronic migraine patients had significantly lower TBUT (11.9 ± 5.9 vs 8.3 ± 6.7; p = 0.30) and higher OSDI scores (25.7 ± 20.1 vs 36.8 ± 18.2). Conclusions This study showed that migraine patients had an increased presence of DED and severe DED compared to controls. Further, increased migraine severity and chronicity were associated with increased subjective symptoms and objective signs of DED. Migraine patients with DED were more disabled.CM patients had more DED symptoms and signs.